Proactive Work Behavior Model in Maximizing More Effective and Efficient Performance: A Conceptual Study as a Guide for Researchers - Gupron, Gupron; Yandi, Andri (Journal of Accounting and Finance Management, 2024)
This study examines the proactive work behavior of employees in an organization. This research consists of several parts. First, the literature review focuses on proactive work behavior. Second, the research model and propositions developed in this research are based on a literature review of previous studies, such as factors that influence proactive work behavior. In the context of proactive work behavior, it plays an important role in organizational behavior theory and research for organizational development. This is because stakeholders will be able to design practical interventions to encourage proactive work behavior based on knowledge. Apart from that, the resulting proactive work behavior will also contribute to personal characteristics (knowledge, abilities, personality) and situational factors (job characteristics, leadership and organizational climate). Thus, overall implementing proactive work behavior can create a dynamic, innovative and productive work environment, which ultimately supports the long-term success of the organization.